2022
DOI: 10.1002/jmv.28156
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors related to COVID‐19 vaccine hesitancy and unwillingness in Canada: A systematic review and meta‐analysis

Abstract: This systematic review and meta‐analysis examined the prevalence and factors associated with vaccine hesitancy and vaccine unwillingness in Canada. Eleven databases were searched in March 2022. The pooled prevalence of coronavirus disease 2019 (COVID‐19) vaccine hesitancy and unwillingness was estimated. Subgroup analyses and meta‐regressions were performed. Out of 667 studies screened, 86 full‐text articles were reviewed, and 30 were included in the systematic review. Twenty‐four articles were included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 65 publications
1
28
2
Order By: Relevance
“…Our meta-analysis revealed that the prevalence of refusal to undergo the COVID-19 vaccination was 12%. Our findings were lower than those reported by Cenat et al and Robinson et al 41,42 In our study, we had a larger sample size than those reported by in these studies. Moreover, studies by Cenat et al and Robinson et al also involved articles that reported COVID-19 vaccination hesitancy.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Our meta-analysis revealed that the prevalence of refusal to undergo the COVID-19 vaccination was 12%. Our findings were lower than those reported by Cenat et al and Robinson et al 41,42 In our study, we had a larger sample size than those reported by in these studies. Moreover, studies by Cenat et al and Robinson et al also involved articles that reported COVID-19 vaccination hesitancy.…”
Section: Discussioncontrasting
confidence: 75%
“…Our study also had a larger sample size compared to previous meta-analyses in a similar context. 41,42 The findings of our study might serve as the initial step to prevent the failure of COVID-19 vaccination programs. By identifying the potential factors associated with refusal to vaccinate against COVID-19, we expect that governments may provide advanced intervention to those populations.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Indeed, there is an urgent need to improve the collection of racial and ethnic data in both general population health surveys and public cancer databases. Despite guidance from the Canadian Institute for Health Information on collecting racial and ethnic data, 79 two recent systematic reviews showed that few population‐based studies on vaccine hesitancy have collected data from non‐White populations and even fewer from Black 80 populations 81 . This observation shows that the color‐blind approach continues even though data revealed the challenges that Black people faced during the COVID‐19 pandemic 82 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite guidance from the Canadian Institute for Health Information on collecting racial and ethnic data, 79 two recent systematic reviews showed that few population-based studies on vaccine hesitancy have collected data from non-White populations and even fewer from Black 80 populations. 81 This observation shows that the color-blind approach continues even though data revealed the challenges that Black people faced during the COVID-19 pandemic. 82 In cancer studies, strategies need to be developed so that every research study conducted in Canada should collect racial and ethnic data.…”
Section: Implications and Conclusionmentioning
confidence: 97%